2019
DOI: 10.1111/ddi.12934
|View full text |Cite
|
Sign up to set email alerts
|

Predicting future distributions of lanternfish, a significant ecological resource within the Southern Ocean

Abstract: Aim Lanternfish (Myctophidae) are one of the most abundant and ecologically important families of pelagic teleosts, yet how these species will respond to climate change is unclear, especially within polar regions. The aim of this study was to predict the impact of climate change on the distribution of Southern Ocean lanternfish and to relate these predicted responses to species traits. Location Circumpolar, 35–75°S. Methods We used MaxEnt ecological niche models to estimate the present and predict the future d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 88 publications
6
53
0
Order By: Relevance
“…Understanding mesopelagic distribution has also been the focus of recent attempts to classify the global biogeography of the mesopelagic zone (Proud et al 2017, Sayre et al 2017, Sutton et al 2017, Rey-gondeau et al 2018. These global studies, and recent work predicting future distributions of lan ternfish at high latitudes (Freer et al 2019), have focused on temperature, salinity, primary production, and surface wind stress as environmental drivers, but have not included light despite a long history of compelling observational studies (i.a. Kampa 1971, Dickson 1972, Tont 1976, Aksnes et al 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding mesopelagic distribution has also been the focus of recent attempts to classify the global biogeography of the mesopelagic zone (Proud et al 2017, Sayre et al 2017, Sutton et al 2017, Rey-gondeau et al 2018. These global studies, and recent work predicting future distributions of lan ternfish at high latitudes (Freer et al 2019), have focused on temperature, salinity, primary production, and surface wind stress as environmental drivers, but have not included light despite a long history of compelling observational studies (i.a. Kampa 1971, Dickson 1972, Tont 1976, Aksnes et al 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Myctophids are also likely to be impacted directly by sustained ocean-warming in the Scotia Sea, with changes in temperature altering their distribution patterns, abundance, life cycles and behavior, which could further affect food web stability in the region (Freer et al, 2019). For example, a recent study found that the Scotia Sea myctophid community adheres to Bergmann's rule, a size-temperature rule whereby species and individuals are larger in colder waters at higher latitudes (Saunders and Tarling, 2018).…”
Section: Impact Of Ocean-warming On Food Web Dynamicsmentioning
confidence: 99%
“…This makes them highly vulnerable to climate change (Peron et al, 2012;Bost et al, 2013Bost et al, , 2015Cristofari et al, 2018). Shifts in their main prey, myctophids, are predicted under future climate change scenarios, with unknown consequences for king penguins (Freer et al, 2019).…”
Section: Ecological Outcomesmentioning
confidence: 99%